Features of local identity of single-industry town residents (the case of the Murmansk Oblast) - Elena V. NEDOSEKA; Galina V. ZHIGUNOVA (Northern Arctic Federal University, 2019)
The article presents an analysis of the local identity of single-industry town residents in the Arctic zone of the Russian Federation (AZRF) in the case of the Murmansk Oblast, which has half the single-industry towns of the Arctic zone. Considering local identity as a EArt of territorial identity, the authors present it as a symbolic sEAce for creating and strengthening the sense of territorial identity. At the same time, according to the authors, the people's identification related to the area of residence contributes to the construction of an effective system of regional interaction. It is one of the critical factors for the sustainable development of territories. According to the results of the study, positive and negative factors of identity manifestation were obtained from the residents of single-industry towns of the surveyed area (questionnaire (n=428), in-depth interviews (n=12)); the assessment of connection with the place of residence and socio-economic status of residents, the degree of attractiveness of cities and migration attitudes of the population were determined. The authors argue that the socio-economic image of the area in the minds of its residents is developing along with the manifestation of their rootedness. A distinctive feature of the local identity of single-industry town residents in the Murmansk Oblast is well-being. It determines the visibility of communication with the place of residence. The increase in prosperity is proportional to the growth of identification with the town, and it is of strategic importance for building regional policies in single-industry towns.